Examining factors affecting employee performance with the mediation of employee learning: Malaysian SME businesses context - Teh, Chee Chong (2020)
The small and medium enterprise (SME) is the backbone of the nation’s economy and government is indeed playing a rigorous role to develop this industry. Most SME businesses are competing to survive in this volatile and fierce market environment. The performance of the employee is one of the success factors in SME businesses. Plenty of research has been conducted on this topic, however, very limited research was conducted on employee learning as the mediator towards employee performance in the Malaysian SME industry. Hence, this research intends to fill the gap. The literature review showed the effects of several factors such as employee learning, employee motivation, working environment, employee work engagement, self-efficacy, employee ability, job satisfaction, and organization support towards employee performance. A theoretical framework was then developed based on the Social Learning Theory which consists of three (3) main aspects, namely Personal Factors, Environmental Factors and Behavioural Factors. 14 hypotheses were developed based on the research framework. This research used the quantitative methodology. A total of 390 valid responses were received for this research. The multiple regression technique was used to test the hypotheses. The results of this research showed that there is a positive and direct relationship between employee motivation, employee ability, self-efficacy, employee work engagement, and employee performance respectively within the Malaysian SMEs. Besides, this research also discovered three (3) new relationships. Firstly, it confirmed that employee learning has the full significant role of a mediator in the relationships between employee motivation and employee performance. Secondly and thirdly, employee learning is found to be a partial mediator in the relationship between employee ability, self-efficacy and employee performance respectively. These newly discovered relationships represent new contributions to the body of knowledge. The findings of this research contribute towards the theoretical and practical aspects.